Evaluation of Reservoir Characteristics of Wells X, Y, Z in the Pliocene Interval of the Tarakan Sub-Basin, Tarakan Basin, North Kalimantan - Hendardi, Rizaldi Primanda; Hidajat, Wahju Krisna; Setyawan, Reddy; Kurniasih, Anis; Qadaryati, Nurakhmi; Khorniawan, Wahyu Budhi; Dalimunte, Hasnan Luthﬁ; Ringga, Anita Galih (Geological Engineering Department Universitas Gadjah Mada, 2024)
The Tarakan Basin is one of the basins that has been producing hydrocarbons since 1901, with nine active oil fields to this day. The exploration of oil and gas in the Tarakan Basin has been ongoing for a considerable amount of time and can be considered as the oldest exploration in Indonesia that continues due to its estimated economically viable reserves based on its geological conditions. Research on the evaluation of reservoir characteristics in the Tarakan Sub-Basin with a Pliocene age interval aims to determine the subsurface lithology and fluid conditions qualitatively and the quantitative characteristics of the reservoir rocks. This study utilizes quantitative petrophysical analysis using a deterministic method with primary data consisting of wireline log data, as well as secondary data including core data, mud logs, biostratigraphy data, drill stem test data, and sidewall core data. Based on the analysis results, the petrophysical properties of the target reservoir in the study area include an average shale volume (VSH) of 16.65% - 29.31%, average effective porosity (PHIE) of 11.80% - 27.09%, which falls into the categories of fair to excellent quality, hydrocarbon saturation ranging from 7.68% - 43.03%, an average permeability value (PERM) of 10.03 mD - 613.29 mD, falling into the categories of good to very good, and a net pay thickness ranging from 4 feet to 16.7 feet, with a total thickness of 67.4 feet containing oil and gas fluids.